Analysing institutional change in environmental governance: exploring the concept of 'institutional work'. Issue 1 (2nd January 2019) - Beunen, R.; Patterson, J.J.
Abstract : Institutional work focuses on the role of actors in creating, maintaining, or disrupting institutional structures. The concept has its origin in organisational studies. In this paper, we rethink and redefine institutional work to make it fit for use in the multi-actor and multi-level context of environmental governance. We survey key approaches to institutional change in the literature, and argue that institutional work should have a central place within this theorising. Drawing on the insights from this literature, we argue that studying institutional work should involve a look at both the actions taken by actors, as well as the resulting effects. We identify a critical need for attention to the fundamentally political character of institutional work, the cumulative effects of action taken by multiple actors, and communicative and discursive dimensions. Overall, the concept of institutional work opens up new possibilities for unpacking the longstanding challenge of understanding institutional change in environmental governance.